(untitled) - Eliza Bertino (Workingham, England, 1993)
This book deals with systematically with object-oriented systems and looks at their data models and languages, and their architecture. It is divided into ten chapters. Chapter 1 is a general introduction to recent trends in the field of databases. Chapter 2 describes object-oriented data models, various semantic extensions to these and the models of the number systems. Chapter 3 covers query languages. Chapter 4 and 5 describe versions and evolution. Chapter 6 deals with authorization models. Chapter 7 and 8 discuss optimization of queries and implementation and access strategies. Chapter 9 describes the architectures of certain systems. Finally, the Summary is a conclusion and covers futures trends in research and development
Cơ sở dữ liệu HĐT
Keywords: database management - computer programs